KEEFEKTIFAN MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KETERAMPILAN KOMUNIKASI INTERPERSONAL SISWA SEKOLAH DASAR - Fauziah, Nida Salma; Imaningtyas, Imaningtyas; Utami, Nidya Chandra Muji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore the effectiveness of the Think Pair Share (TPS) learning model on the interpersonal communication skills of upper-grade elementary school students. The method employed is a Literature Review with a qualitative approach, analyzing 20 scholarly publications published between 2019 and 2025. The analysis results indicate that the TPS model consistently contributes positively to enhancing various aspects of interpersonal communication skills, such as speaking, listening, expressing opinions, as well as fostering cooperation, empathy, and self confidence. The three stages of the TPS model think, pair, and share create a collaborative learning environment that supports social interaction and active idea exchange.